2016
DOI: 10.2217/cer-2015-0009
|View full text |Cite
|
Sign up to set email alerts
|

Effects of alternative interventions among hospitalized, cognitively impaired older adults

Abstract: Findings suggest the TCM is more effective than ASC. However, potential effects of the RNC relative to the TCM warrant further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(29 citation statements)
references
References 60 publications
0
29
0
Order By: Relevance
“…Naylor and colleagues (Naylor et al., , ) have demonstrated that the advanced practice nurse (APN) can play a central role during the transition period after heart failure and with cognitively impaired older adults. A variation of Naylor's Transitional Care Model (TCM) could be an important approach for ISSs.…”
Section: Discussionmentioning
confidence: 99%
“…Naylor and colleagues (Naylor et al., , ) have demonstrated that the advanced practice nurse (APN) can play a central role during the transition period after heart failure and with cognitively impaired older adults. A variation of Naylor's Transitional Care Model (TCM) could be an important approach for ISSs.…”
Section: Discussionmentioning
confidence: 99%
“…In search of high‐level research in transitional care, we also identified four well‐designed studies without randomization. These studies focused on NP‐led interventions for community‐dwelling older adults at high risk of rehospitalization (Condon, Lyca, Duncan, & Bushnell, ; Deniger, Troller, & Kennelty, ; Naylor et al., ; Ornstein, Smith, Foer, Lopez‐Cantor, & Soriano, ). Risk was determined by a combination of cognitive and physical functioning, polypharmacy, social support deficits, falls history, comorbidities, and high‐risk medications.…”
Section: Evidence Reviewmentioning
confidence: 99%
“…Naylor et al. () assessed patients with a diagnosis of dementia or cognitive deficits in a nonrandomized confirmatory study to test the efficacy of TCM‐based interventions on cognitively impaired adults (Table ). Condon et al.…”
Section: Evidence Reviewmentioning
confidence: 99%
See 2 more Smart Citations